2013
DOI: 10.7863/ultra.32.12.2083
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Costotransverse Joint Injections

Abstract: A Computed Tomographically Controlled Cadaveric Feasibility Studyack pain is a common problem with a lifetime prevalence of approximately 80%. [1][2][3] Although thoracic back pain accounts for only 15% to 20% of all back pain syndromes, the disability incurred by patients with thoracic back pain is equal to that experienced by those with cervical or lumbar spinal pain. [3][4][5] Among symptomatic patients presenting with thoracic pain, multiple potential pain generators have been identified, including but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Then, the transducer was moved medially through the transverse process of T12 and L1 to find the facet joint and then upward to the target segment. Meanwhile, Deimel et al 10) and Marhofer et al 11) described a segment identification method using the spinous process of C7. First, the spinous process of C7 was checked with a transducer, which was moved downward to the spinous process of the target segment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the transducer was moved medially through the transverse process of T12 and L1 to find the facet joint and then upward to the target segment. Meanwhile, Deimel et al 10) and Marhofer et al 11) described a segment identification method using the spinous process of C7. First, the spinous process of C7 was checked with a transducer, which was moved downward to the spinous process of the target segment.…”
Section: Discussionmentioning
confidence: 99%
“… 7) Therefore, previous studies on ultrasound-guided thoracic spinal block suggested only the accuracy of contrast material injection at the target facet joint or the paravertebral space as a factor associated with the cause of pain, not the accuracy of target segment identification. 8 9 10) However, with the expanding indications for thoracic spinal nerve block, there has been a growing expectation on favorable results of ultrasound landmark-guided block performed at the definite target segment for conditions, such as facet syndrome associated with thoracic vertebral compression fracture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All ultrasound-guided CTRV joint injections were performed by one pain physician (K.B.Y.) as previously described by Deimel et al [ 10 ]. For image optimization, we identified the transverse process, CTRV joint, rib, and lung in the same plane ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The costovertebral and CTRV joints also significantly contribute to the stability and movement of the thoracic spine, which is not limited to motion of the ribs [ 6 7 ]. Although the CTRV joints are relatively less studied compared to the thoracic facet joints and intervertebral disks, it has been well established that the CTRV joints may produce clinically significant thoracic back pain [ 1 8 9 10 11 ]. Therefore, we hypothesized that the CTRV joints might be a source of pain and that this treatment could lead to clinical improvements.…”
Section: Introductionmentioning
confidence: 99%